Penggunaan Teknik Conservative Sharp Wound Debridement (CSWD) Pada Pasien Osteomielitis Kaki Diabetik - Sephia Rahmawati; Fitri Eka Rahmawati; Ida Maryati; Citra Arista (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
A complication of diabetes that has been going on for a long time and spreads to the bones is called Diabetic Foot Osteomyelitis (DFO). The condition Diabetic Foot Osteomyelitis is associated with advanced peripheral neuropathy accompanied by peripheral arterial disease and foot deformity. The most serious complication of Diabetic Foot Osteomyelitis is amputation of the wound area. The non-operative action that can be carried out is wound care using the Conservative Sharp Wound Debridement (CSWD) technique by removing necrotic tissue, both bone and soft tissue that is infected. The aim of the study was to analyze the results of modern wound care using the CSWD technique in Diabetic Foot Osteomyelitis. The research method uses interviews and observation. The sample used was 1 client Mr. T who experienced Diabetic Foot Osteomyelitis using the Bates-Jensen Wound Assessment Tools (BWAT) wound assessment instrument. The results of this research are that the use of CSWD in debridement is effective in helping the wound healing process, this is proven by a decrease in the BWAT score from 34 to 28.. The conclusion of this study is that the use of the CSWD technique is effective in reducing necrotic tissue and bone that has experienced infection so that it can help the wound healing process.